Turbulent Flow and Heat Transfer in Circular Couette Flows in Concentric Annulus - Shuichi Torii; Wen-Jei Yang (International Journal of Rotating Machinery, 1998)
A numerical study is performed to investigate heat transfer and fluid flow in the hydrodynamically and thermally fully-developed region of an annulus, consisting of a heated rotating inner cylinder and a stationary insulated outer cylinder. Emphasis is placed on the effect of rotation of an inner core on the flow structure and the thermal field. A Reynolds stress turbulence model is employed to determine three normal components of the Reynolds stress and its off-diagonal one. The turbulent heat flux is expressed by Boussinesq approximation in which the eddy diffusivity.for heat is given as functions of the temperature variance t2¯ and the dissipation rate of temperate fluctuations εt. The governing boundarylayer equations are discretized by means of a control volume finite-difference technique and numerically solved using the marching procedure. An inner core rotation causes an amplification of the three normal components of the Reynolds stress over the whole cross section, resulting in a substantial enhancement in the Nusselt number.